PERKEMBANGAN PENELITIAN KUALITAS AUDIT DI INDONESIA - Faradilla, Widya Septi; Setiawan, Doddy (Ultimaccounting Jurnal Ilmu Akuntansi, 2025)
Abstract— In the current competitive global landscape, the demand for transparency and accountability in financial reporting has significantly increased. Investors require accurate and reliable information to make well-informed decisions, while regulatory authorities have heightened oversight by enforcing stricter regulations and penalties for non-compliance. This environment calls for robust financial reporting systems and independent audits to maintain high standards of financial disclosure. High-quality audits are essential for maintaining stakeholder trust. However, the prevalence of fraud cases in Indonesia raises concerns about the effectiveness of current audit practices and the ability of auditors to detect and prevent fraud. As a result, the importance of audit quality has garnered increased attention from researchers. This study examines the trends in audit quality research in Indonesia as published in SINTA 2 journals from 2015 to 2024. The research employs the Charting the Field method, examining 108 articles categorized by topic and research method. The results reveal that the determinants of audit quality most frequently examined are independence, audit rotation, audit tenure, audit fees, and competence. In contrast, the most commonly investigated consequential variable is earnings management. Keywords: Audit Quality; Literature Review; Charting the Field; Review and Mapping; Research Trends